(untitled) - Lee, Henry (United States, 1989)
The recommendations in this document are based on our experience and best scientific judgment. It is our hope that the "routine" and experimental sediment bioaccumulation tests, as well as aid regulators in determining when bioaccumulation tests are needed, in evaluating the QA/QC procedures of such tests, and in interpreting the results.
Keywords: Dredging spoil,Soil biochemistry,Lợi nhuận nạo vét sông,Sinh hóa học đất; Environmental aspects,Khía cạnh môi trường